Solithromycin in Children and Adolescents With Community-acquired Bacterial Pneumonia. Issue 7 (7th June 2022) - Lang, Jason E.; Hornik, Christoph P.; Elliott, Carrie; Silverstein, Adam; Hornik, Chi; Al-Uzri, Amira; Bosheva, Miroslava; Bradley, John S.; Borja-Tabora, Charissa Fay Corazon; Di John, David; Mendez Echevarria, Ana; Ericson, Jessica E.; et al.
Abstract : Background: Solithromycin is a new macrolide-ketolide antibiotic with potential effectiveness in pediatric community-acquired bacterial pneumonia (CABP). Our objective was to evaluate its safety and effectiveness in children with CABP. Methods: This phase 2/3, randomized, open-label, active-control, multicenter study randomly assigned solithromycin (capsules, suspension or intravenous) or an appropriate comparator antibiotic in a 3:1 ratio (planned n = 400) to children 2 months to 17 years of age with CABP. Primary safety endpoints included treatment-emergent adverse events (AEs) and AE-related drug discontinuations. Secondary effectiveness endpoints included clinical improvement following treatment without additional antimicrobial therapy. Results: Unrelated to safety, the sponsor stopped the trial prior to completion. Before discontinuation, 97 participants were randomly assigned to solithromycin (n = 73) or comparator (n = 24). There were 24 participants (34%, 95% CI, 23%–47%) with a treatment-emergent AE in the solithromycin group and 7 (29%, 95% CI, 13%–51%) in the comparator group. Infusion site pain and elevated liver enzymes were the most common related AEs with solithromycin. Study drug was discontinued due to AEs in 3 subjects (4.3%) in the solithromycin group and 1 (4.2%) in the comparator group. Forty participants (65%, 95% CI, 51%–76%) in the solithromycin group achieved clinical improvement on the last day of treatment versus 17 (81%, 95% CI, 58%–95%) in the comparator group. The proportion achieving clinical cure was 60% (95% CI, 47%–72%) and 68% (95% CI, 43%–87%) for the solithromycin and comparator groups, respectively. Conclusions: Intravenous and oral solithromycin were generally well-tolerated and associated with clinical improvement in the majority of participants treated for CABP.